Heat-induced aging of agar solutions: Impact on the structural and mechanical properties of agar gels. (March 2017) - Mao, Bosi; Bentaleb, Ahmed; Louerat, Frédéric; Divoux, Thibaut; Snabre, Patrick
Abstract: Thermoreversible gels are commonly prepared by cooling down to ambient temperature, aqueous polymer solutions first brought to a boil for a short time. Here, we study the effect of the latter duration on the subsequent gelation of an agar solution. Increasing the incubation time at high temperature ( T = 80 °C) from hours to a few days leads to the hydrolysis and the oxidation of the polysaccharides, and results in the decrease of the viscosity and the pH of the solution. Samples withdrew at different incubation times are cooled down to form gels whose structure and mechanical properties are systematically determined. Cryoelectron microscopy and X-ray diffraction experiments reveal that agar gels formed from solutions of increasing incubation times, display a coarser microstructure composed of micron-sized foils which result from the condensation of the polysaccharides, and contrast with the fibrous-like microstructure of gels prepared from a fresh agar solution. Along with structural changes, a prolonged incubation time of the agar solution at T = 80 °C leads to weaker gels than those made from fresher solutions, and extensive macro-indentation experiments coupled to direct visualization show that the gel rupture scenario turns from brittle to ductile-like as the incubation time increases. Our study suggests that the incubation time of agar solutions at high temperature could be used as an external control parameter to tune the mechanical properties of agar-based gels. Graphical abstract: Highlights: Prolonged incubation of agar solution at high temperature (80 °C) leads to the solution aging. Polysaccharides undergo hydrolysis, oxidation and intermolecular condensation. Increasing incubation times of agar solution leads to delayed gelation upon cooling. Resulting gels show a coarser microstructure, and break following a ductile rupture scenario.